L’emprunt au féminin : réseaux de femmes et associations d’épargne à Damas - Friederike Stolleis (Revue des Mondes Musulmans et de la Méditerranée)
The lives of many Damascene women are imbedded in a network of social relations which are established and maintained through regular visits, the most formal of whixh are women’s reception day. In recent times, these networks often include the participation in a savings association which helps the women to cope with the economic challenges of daily life. The article describes how women have modified their ways of socialising over time and adapted it to a changing environment. It explains how the savings association function as an informal credit system as well as being a framework for socialising. The personal relations thus established between its members form a network which acts is used an insurance against the difficulties and uncertainties of life in a system in which very often basic social services are insufficient.